DIGITALISASI PERTANAHAN DAN PENDAFTARAN TANAH ELEKTRONIK: EVALUASI EFEKTIVITASNYA DALAM MENEKAN MAFIA TANAH DI INDONESIA - Akbar Emirsyarif Machfud; Suparjo Suparjo (Jurnal Ilmiah Advokasi, 2025)
The land registration system in Indonesia, which is still dominated by paper-based databases, is considered no longer capable of optimally guaranteeing legal certainty of land rights. Outdated data, weak system integration, and limited access to information open the door to abuse of authority and manipulation of land data. These conditions are exploited by land mafia to carry out illegal practices, such as document forgery and the issuance of duplicate certificates, which ultimately harm landowners and undermine public trust in the national land system. This study aims to analyze the effectiveness of land digitization and electronic land registration in minimizing the practices of land mafia in Indonesia. The research method used is normative legal research with a regulatory and conceptual approach, supplemented by an analysis of digital land policy. The results show that electronic land registration has the potential to increase transparency, data accuracy, and land administration accountability, thereby closing the loopholes that have been exploited by land mafia. However, the effectiveness of this system still faces challenges in terms of infrastructure readiness, human resource quality, and regulatory harmonization. Therefore, strengthening the electronic land registration system needs to be accompanied by institutional reform and consistent law enforcement in order to achieve legal certainty and protection of land rights.Keywords: Electronic Land Registration; Land Digitalization; Land Mafia; Legal Certainty; Land Administration